Testicular cancer in two brothers of a quadruplet: a case report and a review of literature - Ulytė, Agnė; Ulys, Albertas; Sužiedėlis, Kęstutis; Patašius, Aušvydas; Smailytė, Giedrė (Acta medica Lituanica, 2017)
Introduction. Testicular cancer and a multiple birth are both rare events, and the risk of testicular cancer is increased in twins. In Lithuania, only five quadruplets have been recorded since the middle of the 20th century. In this report, we present two rare events in one family: testicular cancer in two brothers of a quadruplet (three brothers and a sister). Case description. Both patients were diagnosed at 21 years of age and died within two years from the  diagnosis despite treatment. The  third symptomless brother did not have testicular pathology. We also review the  risk factors associated with testicular cancer, and the  proposed hypotheses how a multiple birth results in an increased risk. The most consistent risk factors for testicular cancer are cryptorchidism, prior history of testicular cancer, and a positive familial history. According to different studies, the risk of testicular cancer in twins is higher from 22% to 30%, compared to the general population. Conclusions. To our knowledge, we have presented the first case of testicular teratoblastoma in brothers of a quadruplet.
Keywords: testicular cancer; quadruplet; multiple birth; risk factors